2020
DOI: 10.1101/2020.09.29.20202416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virus evolution affected early COVID-19 spread

Abstract: As the SARS-Cov-2 virus spreads around the world afflicting millions of people, it has undergone divergent genetic mutations. Although most of these mutations are expected to be inconsequential, some mutations in the spike protein structure have been hypothesized to affect the critical stage at which the virus invades human cells, which could affect transmission probability and disease expression. If true, then we expect an increased growth rate of reported COVID-19 cases in regions dominated by viruses with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…This naïve analysis picked strain 19B as having a lower transmission rate than other strains ( P = 0.014, Supplementary Methods: Analysis of Nextstrain metadata of SARS-CoV-2 strains). Strain 19B does not have the G614 mutation, although strain 19A (also without the G614 mutation) did not have lower transmission than G614-containing strains, suggesting possible differences among strains separate from or in addition to the G614 mutation 25 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This naïve analysis picked strain 19B as having a lower transmission rate than other strains ( P = 0.014, Supplementary Methods: Analysis of Nextstrain metadata of SARS-CoV-2 strains). Strain 19B does not have the G614 mutation, although strain 19A (also without the G614 mutation) did not have lower transmission than G614-containing strains, suggesting possible differences among strains separate from or in addition to the G614 mutation 25 .…”
Section: Resultsmentioning
confidence: 94%
“…3). This uncertainty underscores the need for more information about strain differences affecting SARS-CoV-2 transmission 23,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, quantitative estimates of the basic reproductive number R 0 from infection incidence data suggest that viruses bearing S(G614) are 31% more transmissible than D614, although this analysis did not consider the effect of concomitant changes at other loci in the circulating viral strains [ 41 ]. Various studies have identified co-segregation of changes in other viral genes along with the D614G mutation in spike, such as the P323L mutation in the viral polymerase RdRp which may attenuate replication to compensate for the increased transmissibility of D614G viruses [ 40 , 42 , 43 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…One recent study in Galway reported no increase in the rate of presentations of self-harm/suicidal ideation but noted an increase in the lethality of presentations between March 1 st and May 31 st 2020 compared to the same time period (McIntyre et al, 2020. There was no evidence of an increase in the actual suicide rate in the Cork area in March-August 2020 (N=15) compared to the same time period in 2019 (N=15), based on real-time surveillance of suicide in Cork (Corcoran, 2020),…”
Section: Discussionmentioning
confidence: 90%